173k views
3 votes
1. Solve for x:
3(2x – 1) – 10 = 8 + 5x
A. -7
B. -3
C. 19
D. 21

User Tim Nguyen
by
4.1k points

2 Answers

3 votes

Answer:

(D) 21

Step-by-step explanation:

3(2x−1)−10=8+5x

Step 1: Simplify both sides of the equation.

3(2x−1)−10=8+5x

(3)(2x)+(3)(−1)+−10=8+5x(Distribute)

6x+−3+−10=8+5x

(6x)+(−3+−10)=5x+8(Combine Like Terms)

6x+−13=5x+8

6x−13=5x+8

Step 2: Subtract 5x from both sides.

6x−13−5x=5x+8−5x

x−13=8

Step 3: Add 13 to both sides.

x−13+13=8+13

x=21

User Srikanth Gowda
by
4.5k points
0 votes

Answer:

D. 21

Step-by-step explanation:

Given equation:
\[3(2x – 1) – 10 = 8 + 5x\]

Simplifying:


\[6x – 3 – 10 = 8 + 5x\]

=>
\[6x – 13 = 8 + 5x\]

=>
\[6x – 5x = 8 + 13\]

=>
\[(6 – 5)x = 21\]

=>
\[x = 21\]

Verifying by substituting the value of x in the equation:

Left Hand Side:
\[3(2x – 1) – 10\]


\[3(2*21 – 1) – 10\]

=
\[3(42 – 1) – 10\]

=
\[3(41) – 10\]

=
\[123 – 10\]

=
\[113\]

Right Hand Side:
\[8 + 5x\]

=
\[8 + 5*21\]

=
\[8 + 105\]

=
\[113\]

So, Left Hand Side = Right Hand Side when x=21.

User Enriquein
by
4.5k points